Angiogênese em neoplasias epiteliais corticais renais: estudo de 41 casos - Suzigan, Sueli (2002)
Introduction. Tumor growth and metastasis depend greatly on angiogenesis. There are several angiogenic growth factors able to induce new vessels in renal tumors, but the most important are vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (b-FGF). The aim of our study was to investigate expression of b-FGF and to quantify microvessel density (MVD) in oncocytomas and renal cell carcinomas (RCCs) and to relate these parameters of tumor vascularity to other clinicopathological features. Material and Methods. b-FGF and CD31 immunostaining were performed on formalin-fixed paraffin-embedded archival tissues from Larpac Laboratories files, including 36 RCCs (10 conventional, 10 papillary, 8 sarcomatoid, and 8 chromophobe) and 5 oncocytomas. Angiogenesis was quantified microscopically by two independent observers. Results. b-FGF was positive in all five oncocytomas and only in seven of 36 RCCs: 5 of conventional type, 1 papillary, and 1 chromophobe. All sarcomatoid carcinomas were negative. The expression of b-FGF was not related to tumor size, grade, stage, or short survival in either group. MVD mean value was 124.16 ± 50.1 in oncocytomas and 91.54 ± 52.4 in RCCs. The pattern of vascularization observed in oncocytomas was characterized by a fine vascular network around groups of tumor cells although in RCCs the microvessels tended to be more disorganized. When analyzing only carcinomas, patients who died within 12 months after the diagnosis had a tumoral MVD mean value significantly higher (124.12 ± 75.2) than that observed in patients who were still alive one year after diagnosis (80.34 ± 37.8). ix Conclusion. We demonstrate that b-FGF is expressed more often in oncocytomas than in RCCs but MVD is similar in both groups of tumors. The high expression of b-FGF in oncocytomas may reflect the peculiar pattern of vascularization of these tumors. High MVD in rapidly lethal RCCs is an indication that angiogenesis may be correlated with the degree of malignancy of these tumors.